2017
DOI: 10.2147/idr.s144296
|View full text |Cite
|
Sign up to set email alerts
|

Association between the <em>IL-6</em> gene polymorphism and tuberculosis risk: a meta-analysis

Abstract: BackgroundThe gene polymorphism of interleukin-6 (IL-6) has been shown to be implicated in tuberculosis susceptibility in many studies, but with conflicting results. This study aimed to provide more accurate estimation of the relationship between IL-6 gene polymorphism and tuberculosis risk through a meta-analysisMethodA literature search was performed in PubMed, EMBASE, and other databases. Data were retrieved, and pooled odds ratio (OR) with 95% CI were calculated. Statistical analyses were performed by usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 36 publications
(55 reference statements)
0
6
1
Order By: Relevance
“…More studies should be performed to investigate the mechanism of how IL-6 polymorphism regulates IL-6 production and plays a role in tuberculosis susceptibility. 6 The current study has not supported a role for IL-6 gene polymorphism in patient susceptibility to MDR pulmonary tuberculosis, since contrasting both genetic allelic variation in MDR TB group against both control and drug-sensitive TB patients has failed to show statistical significance. In accordance with these findings, Milano found no significant association between susceptibility to MDR TB and genotype or allelic polymorphism associating IL-6 (-572G/C) gene locus.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…More studies should be performed to investigate the mechanism of how IL-6 polymorphism regulates IL-6 production and plays a role in tuberculosis susceptibility. 6 The current study has not supported a role for IL-6 gene polymorphism in patient susceptibility to MDR pulmonary tuberculosis, since contrasting both genetic allelic variation in MDR TB group against both control and drug-sensitive TB patients has failed to show statistical significance. In accordance with these findings, Milano found no significant association between susceptibility to MDR TB and genotype or allelic polymorphism associating IL-6 (-572G/C) gene locus.…”
Section: Discussioncontrasting
confidence: 67%
“…Therefore, GG genotype may be associated with less risk of pulmonary TB in comparison with GC and CC genotypes. In accordance with these findings, Wang 6 in their meta-analysis have found that genotype GG is associated with significantly more susceptibility to pulmonary TB than both GC and CC genotypes. In agreement with the finding of the current study, it has been shown than genotype CC is associated with less risk of pulmonary tuberculosis.…”
Section: Discussionmentioning
confidence: 59%
“…First, it may be due to a different genetic background, such as frequencies of the AA genotype at rs3805246. Also, different environmental factors can potentially induce various gene modifications [ 22 , 23 ]. Furthermore, gene SNPs differ in individual populations, regions, and races or ethnicities [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the previous study has provided important clues that the host genetics was indispensable for the development of TB [8]. Previous studies had reported that genetic variation of cytokines would be involved in the susceptibility to TB, such as interleukin 6 [9], interleukin 10 [10], and interleukin 17 [11]. Meanwhile, genetic polymorphism of the vitamin D receptor was also reported in association with TB [12].…”
Section: Introductionmentioning
confidence: 99%